Assessment of land uses on the urban littoral easement of Pujada Bay protected seascape - Valdesco, Dolores D.
In an attempt to portray the conflict between urbanization and protection use, the present study tried to describe the existing spatial uses in the urban water easement of 3 meters from the highest high tide of Pujada Bay Protected Seascape in Mati, Davao Oriental, particularly in the barangays of Badas, Central, Matiao and Dahican.With the objectives of determining the land uses, their factors of existence, degree of compliance to the Water Code of the Philippines and compatibility to the protected status of the bay, this study assessed the different land uses such as settlement use with the commercial, institutional and industrial uses in it, infrastructure, parks recreational/tourism, agriculture, and mangrove uses in the urban water easement, which is also considered as the urban buffer zone of the bay in the absence of a declared buffer area by the Protected Area Management Board. The survey of the study revealed that the water easement is encroached with settlements which has caused pollution to the bay and degraded the coastal scenery. Majority (73-80%) of the encroaching settlers are not made aware and involved in the protected area management. Gathered opinions and perceptions of the urban easement settlers bared that they themselves realized the negative impacts of settlements on the shoreline to the seascape but are forced to stay on the site due to socio-economic reasons. It is concluded in this study that institutional laxity of policy implementation on land use regulation contributed to proliferation of informal settlements in the easement and foreshore of Pujada Bay which caused the deterioration of its ecological integrity which in turn could jeopardize its vital role as biodiversity habitat and could forfeit its potentials for ecotourism, which is one function of a protected seascape.
Keywords: Pujada Bay (Mati, Davao Oriental) Philippines -- Land use